Characteristics of Power Engineering Plant-1 (PEP-1) - N. V. Panteley (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper presents a new power engineering plant which is designed for desired obtaining important technological products from products of fuel combustion. The paper also considers an influence of regime factors on expenditure characteristics of Power Engineering Plant-1. Amount of the obtained technological products has been also estimated in the paper.